Not just old wine in new bottles: Polygenic liability for ADHD is associated with electrophysiological affective-motivational processing beyond anxiety, depression, and ODD - Kristóf Ágrez; Zsombor Visky; György Hámori; Mária Takács; Attila J. Pulay; János M. Réthelyi; Nóra Bunford (Translational Psychiatry)
Abstract In attention-deficit/hyperactivity disorder (ADHD), emotional features account for heterogeneity and exacerbate severity of behavioral and functional impairments, beyond cognitive and comorbidity features. Yet, debate remains about the extent to which, in ADHD, such emotional features are a “core feature”, i.e. whether ADHD should be conceptualized as encompassing difficulties with regulating not only activity, attention, and impulses but also processing and regulating emotions. We aimed to address this issue by examining the extent to which in adolescents, ADHD polygenic scores (PGSs) are associated with electrophysiological indices of affective-motivational processing, measured during a monetary punishment/reward feedback paradigm. ADHD PGSs were negatively associated, in n = 166 adolescents (M age = 15.76 years, SD = 1.07; 42.77% girls), with amplitude values of an occipitoparietal event-related potential (i.e. late positive potential) and were positively associated, in n = 84 adolescents (M age = 15.76 years, SD = 1.05; 41.67% girls), with fronto-centro-parietal alpha event-related desynchronization. Across analyses, covariates were anxiety, depression, and ADHD with comorbid disruptive behavior disorder PGSs; ADHD, internalizing, and oppositional defiant disorder severity; childhood maltreatment; current ADHD medication; and baseline values of the outcome. Findings were replicated in sensitivity analyses with blocks of conceptually related covariates entered separately. In adolescents, electrophysiological indices of affective-motivational processing are associated principally with genetic liability for ADHD but not comorbidity genetic liability or comorbidity manifest symptoms.